Influence of Mechanical Ventilation on the Incidence of Pneumothorax During Infraclavicular Subclavian Vein Catheterization: A Prospective Randomized Noninferiority Trial. (September 2016) - Kim, Eugene; Kim, Hyun Joo; Hong, Deok Man; Park, Hee-Pyoung; Bahk, Jae-Hyon
Abstract : BACKGROUND: It remains unclear whether we have to interrupt mechanical ventilation during infraclavicular subclavian venous catheterization. In practice, the clinicians' choice about lung deflation depends on their own discretion. The purpose of this study was to assess the influence of mechanical ventilation on the incidence of pneumothorax during infraclavicular subclavian venous catheterization. METHODS: A total of 332 patients, who needed subclavian venous catheterization, were randomly assigned to 1 of the 2 groups: catheterizations were performed with the patients' lungs under mechanical ventilation (ventilation group, n = 165) or without mechanical ventilation (deflation group, n = 167). The incidences of pneumothorax and other complications such as arterial puncture, hemothorax, or catheter misplacements and the success rate of catheterization were compared. RESULTS: The incidences of pneumothorax were 0% (0/165) in the ventilation group and 0.6% (1/167) in the deflation group. The incidence of pneumothorax in the deflation group was 0.6% higher than that in the ventilation group and the 2-sided 90% confidence interval for the difference was (−1.29% to 3.44%). Because the lower bound for the 2-sided 90% confidence interval, −1.29%, was higher than the predefined noninferiority margin of −3%, the inferiority of the ventilation group over the deflation group was rejected at the .05 level of significance. Other complication rates and success rates of catheterization were comparable between 2 groups. The oxygen saturation dropped below 95% in 9 patients in the deflation group, while none in the ventilation group ( P = .007). CONCLUSIONS: The success and complication rates were similar regardless of mechanical ventilation. During infraclavicular subclavian venous catheterization, interruption of mechanical ventilation does not seem to be necessary for the prevention of pneumothorax.